Manajemen Pembelajaran Berbasis Riset di Madrasah (Studi Kasus di Madrasah Aliyah Negeri Kudus Indonesia) - Haryanto Haryanto; Isrohmawati Isrohmawati (Mau`izhah : Jurnal Kajian Keislaman, 2023)
This research aims to describe the planning, implementation, and evaluation of research-based madrasah learning management as well as supporting and inhibiting factors at Madrasah Aliyah Kudus in Indonesia. This research is a qualitative descriptive study. Primary data was taken from 15 teachers, school principals, and 90 students. Secondary research data is in the form of documents, notes, archives, and madrasa profiles, as well as learning outcomes reports. Data collection was carried out through interviews, observation, and documentation. Data were analyzed using the Miles and Huberman interactive model with data collection, reduction, display, and drawing conclusions. Learning management planning is adapted to the 2013 Curriculum following the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 23 of 2016 to fulfill aspects of teacher professional competence. In its implementation, it applies principles of student-centered learning. Teachers act as mediators and motivators to make students active, creative, and innovative. The evaluation includes knowledge, skills, and attitudes. Assessment is carried out through daily assessments, mid-semester, and final assessments. Supporting factors include the development of sophisticated technology, subject collaboration, and student creativity and innovation. The inhibiting factors are the need for supporting media, students' abilities, self-confidence, interest in reading, and inadequate facilities and infrastructure.